(untitled) (Bangladesh Medical Journal, 2019)
Optical urethrotomy has been considered standard therapy for anterior urethral stricture since its introduction in 1976. Now optical internal urethrotomy (OIU) with intralesional triamcinolone injection is a safe and effective, minimally invasive therapeutic modality. The aim of the study is to compare the outcome of OIU alone and OIU with intralesional triamcinolone injection in the treatment of anterior urethral stricture. This Quasi Experimental study was carried out among 50 male patients with bulbar urethral stricture in the Department of Urology, Dhaka Medical College Hospital, Dhaka, over a period of six months. The age range of the patients were 32-46 years and patients were divided equally into two groups, OIU with and without intralesional triamcinolone acetonide injection as Group- A (experimental group, 25 patients) and Group- B (control group, 25 patients). Post-operative evaluation was done on the basis of history and uroflowmetry. Retrograde urethrography and micturating cystourethrography were done only in patient who developed obstructive voiding problems or flow rate below 10 ml/second. Follow up was done at regular interval on 7th day, 3rd month and 6th month. Post-operative outcomes were compared between two groups. Post-operative infection was significantly higher among those OIU with intralesional Triamcinolone acetonide injection (8%) than patients without intralesional Triamcinolone acetonide injection (4%). Per operative extravasations of urine were significantly higher among those without intralesional Triamcinolone acetonide injection (4%) than subjects with intralesional Triamcinolone acetonide injection. Extravasation not influenced by steroid but this patient subsequently suffered recurrence of stricture. In Group-A, pre and post-operative Q-max were 10.25±2.21 and 22.11±2.96 ml/sec respectively. In Group-B, pre and post-operative follow up Q-max were 10.37±2.55 and 19.54±2.65 mi/sec respectively. In Group-A, pre and post-operative voiding time was 85.20±4.20 and 27.10±3.36 sec respectively. In Group-B, pre and post-operative follow up voiding time were 86.37±4.55 and 31.45±2.55 sec respectively. Post-operative recurrences of stricture were significantly higher among those without intralesional Triamcinolone acetonide injection (24%) than subjects with intralesional Triamcinolone acetonide injection (12%). Post-operative it seems that triamcinolone injection after OIU is safe method to prevent the recurrence of urethral stricture Bangladesh Med J. 2019 Jan; 48 (1): 31-38